2004
DOI: 10.1001/jama.292.6.721
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Eliminating Ocular <EMPH TYPE="ITAL">Chlamydia trachomatis</EMPH> With Repeat Mass Antibiotic Treatments

Abstract: ASS ANTIMICROBIAL ADministrations have been used in several control programs and have been contemplated for many others. They have proven to be effective against some parasitic diseases (eg, onchocerciasis and filariasis), but at times have not lived up to expectations (eg, malaria). 1-3 Various forms of mass treatment have been used for bacterial diseases, including sexually transmitted chlamydia and syphilis. 4,5 The World Health Organization (WHO) 6 and its partners are now using repeated mass azithromycin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
132
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(142 citation statements)
references
References 18 publications
8
132
1
Order By: Relevance
“…Thus, if achievable, local elimination of infection would be an important end point. Mathematical models suggest that local elimination of infection is possible even in severely affected communities if antibiotics are distributed frequently enough and to a large enough portion of the community [3,4]. In villages with low rates of infection, у1 treatments have come close to eliminating infection [5][6][7].…”
Section: The World Health Organization Has Distributed Millions Of Domentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, if achievable, local elimination of infection would be an important end point. Mathematical models suggest that local elimination of infection is possible even in severely affected communities if antibiotics are distributed frequently enough and to a large enough portion of the community [3,4]. In villages with low rates of infection, у1 treatments have come close to eliminating infection [5][6][7].…”
Section: The World Health Organization Has Distributed Millions Of Domentioning
confidence: 99%
“…In villages with low rates of infection, у1 treatments have come close to eliminating infection [5][6][7]. In areas of hyperendemicity, if infection is not eliminated from a community, it can clearly return, even if a decrease to a low rate of infection is achieved [4,8,9]. To date, no study has demonstrated that infection can be locally eliminated from all members of a severely affected community.…”
Section: The World Health Organization Has Distributed Millions Of Domentioning
confidence: 99%
“…Further study of this and other chlamydial antigens and of their immune correlates of protection in immunoepidemiological cohort investigationsespecially ones that include sexually active adolescents-are highly desirable. Study designs could incorporate cohorts of commercial sex workers, such as that undertaken here, or communities in which trachoma is hyperendemic, where the incidence of reinfection following mass treatment has approached an astounding rate of 12.3% per month [50]. In either situation, it should be feasible to correlate baseline immunological measurements with the risk of C. trachomatis infection, because of the high risk of reinfection.…”
Section: Hazard Ratios (Hrs) and 95% Confidence Intervals (Cis) Fromentioning
confidence: 99%
“…Mass distribution of oral azithromycin is effective in reducing the burden of ocular Chlamydia in a community. [2][3][4] Mass azithromycin treatments are also effective for several systemic infections, and may even reduce childhood mortality. [5][6][7] Furthermore, azithromycin is thought to be well tolerated in most persons.…”
mentioning
confidence: 99%